2015
DOI: 10.1016/j.concog.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The content of recurrent dreams in young adolescents

Abstract: Studies on children's recurrent dreams have been largely anecdotal and based on adults' recollections of dreams experienced during childhood. We collected 102 reports of recurrent dreams from a sample of young adolescents aged between 11 and 15 years and scored the narratives using a range of content measures, including in relation to the threat simulation theory (TST) of dreaming. The most frequently reported themes involved confrontations with monsters or animals, followed by physical aggressions, falling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The themes identified in the current study reflect previously identified content in nightmares and bad dreams, including aggression, conflict, death, and unrealistic environments (Gauchat, Séguin, McSween‐Cadieux, & Zadra, ; Robert & Zadra, ). Although the majority of the content was negative, more positive content such as Attempts to Change Behavior and Successful Escape indicate that positive outcomes, however brief they may be, do occur.…”
Section: Discussionsupporting
confidence: 76%
“…The themes identified in the current study reflect previously identified content in nightmares and bad dreams, including aggression, conflict, death, and unrealistic environments (Gauchat, Séguin, McSween‐Cadieux, & Zadra, ; Robert & Zadra, ). Although the majority of the content was negative, more positive content such as Attempts to Change Behavior and Successful Escape indicate that positive outcomes, however brief they may be, do occur.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, emotions are the element that is most likely to influence PTSD dreams; up to 80% of dreams replay trauma-related emotions, irrespective of whether these replicate other trauma features ( 28 ). Idiopathic nightmares, while not replicating prior trauma per se , are similar in that they produce recurrent, dysphoric themes ( 29 ) that relate to waking stress and emotional concerns ( 30 ). In light of such parallels, distinctions between replicative and idiopathic nightmares need reevaluation.…”
Section: Explaining Idiopathic Nightmaresmentioning
confidence: 99%
“…Studies investigating the emotional content of nightmares have found that fear was the predominant emotion reported by those who experienced nightmares, followed by extreme anger or sadness [23] Another study by Köthe and Piotrowsky [24] found that state anxiety was significantly elevated on following days after a nightmare compared with days following sleep on an undisturbed night. One study investigating the content of nightmares in adolescents contained mostly scary and threatening content, such as facing dangerous beasts or monsters, being physically attacked or being chased [25]. Thus, as shown in previous studies, nightmares are most likely to trigger the emotions of fear and anxiety.…”
Section: Nightmares and Negative Emotionsmentioning
confidence: 83%